PENGARUH CORPORATE GOVERNANCE, PROFITABILITAS, DAN KARAKTERISTIK EKSEKUTIF PADA TAX AVOIDANCE PERUSAHAAN MANUFAKTUR - Maharani, I Gusti Ayu Cahya; Suardana, Ketut Alit (E-Jurnal Akuntansi; Vol 9 No 2 (2014), 2014)
Tax avoidance is mostly done by the taxpayer because it is legal. There are several factors, the corporate governance, profitability and executive characteristics. This research was conducted at the companies listed on the Stock Exchange in the observation period 2008-2012. Sampling method used was purposive sampling method with a sample of 37 companies during the observation period of 5 years in a row for a total of 159 samples. Based on the results of multiple linear regression analysis, the results showed that the variables that affect negatively the proportion of commissioners, quality audit, the committee audit, and ROA, while the positive effect on the company's risk of tax avoidance that do manufacturing companies listed in Indonesia Stock Exchange observation period 2008-2012.
Keywords: corporate governance,profitability, executive characteristics, tax avoidance